ЕФЕКТИВНІСТЬ ІНОКУЛЯЦІЇ НАСІННЯ РІЗНИХ СОРТІВ ЛЬОНУ ОЛІЙНОГО В УМОВАХ ЛІВОБЕРЕЖНОГО ПОЛІССЯ - Локоть, О. Ю.; Селінний, С. М.; Пархоменко, М. М.; Логоша, О. В. (Institute of Agrocultural Microbiology and Agro-industrial Manufacture of NAAS of Ukraine, 2024)
Objective. Determine the peculiarities of the growth and development of plants of differently ripening varieties of common flax and the formation of their harvest under the conditions of the Left Bank Polissia after bacterization of seeds with Polimiksobacteryn. Methods. Field experiment (the study was carried out on sod-medium-podzolic loamy soil; the area of the sowing plot is 60 m2, the area of the accounting plot is 25 m2, repetition is four times). In the experiments, 7 varieties of common flax were used (early-ripening: Debiut, medium-ripening: Pivdenna Nich, Aisberh, Orfei and late-ripening: Baikal, Ural and Zolotystyi). Microbial preparation Polimiksobacteryn based on Paenibacillus polymyxa КВ was used for bacterization of flax seeds. The experiment was carried out against the background of mineral nutrition with N15P30K45, fertilizers were applied under presowing soil treatment. Results. On average, over three years, pre-sowing inoculation of flax seeds with Polimiksobacteryn contributed to the growth of the total height of plants versus controls (without inoculation): in the ’fir-tree’ phase by 1.4 cm (11.1 %), in the period of rapid growth by 2.1 cm (10.1 %), budding — by 2.1 cm (7.5 %), flowering — by 2.4 cm (6.8 %) and full ripening — by 2.3 cm (5.5 %). The use of Polimiksobacteryn contributed to an increase in the number of pods on the plant by 1.9 pcs. (16.1 %) and weight of 1000 seeds by 0.13 g (2.3 %) versus the control. The increase in the yield of straw of the studied varieties in the variants with Polimiksobacteryn was on average 0.33 t/ha, which is 14.2 % higher than in the control variants (without inoculation). The yield of flax seeds also increased after bacterization. On average, increase in the different varieties versus the controls was 0.23 t/ha (25 %). The maximum yield of seeds in an average of three years was obtained with the early-ripening Debiut variety, it exceeded the yield of other varieties in the variant with bacterization by 0.03–0.28 t/ha (2.4–28.0 %) and amounted to 1.04 t/ha. Conclusion. According to the results of study, in the zonal conditions of the Left Bank Polissia of Ukraine, it was established that the use of the biological preparation Polimiksobacteryn results in the highest yield of common flax varieties of different types of ripening, even under unfavourable weather conditions of the growing season.